The biblical narrative in the Annales of Sa'īd ibn Baṭrīq and the question of medieval Byzantine-Orthodox identity - Simonsohn, Uriel I. (Islam and Christian-Muslim relations, 2011)
This article pursues a close examination of the biblical narrative in Sa?īd Ibn Baṭrīq's (Eutychius of Alexandria, d. 940) historiographic work, the Annales, to reveal a wide range of sources that were available either to the patriarch himself or to an intermediate source on which he relied. These include not only a rich Judaeo-Christian lore but also a rather significant segment of Muslim materials, most notably tales of the prophets (qiṣaṣ al-anbiyā'). The Muslim trappings of some of the Judaeo-Christian apocrypha found in Ibn Baṭrīq's narrative suggest that we are dealing with a Christian writer who made use of Judaeo-Christian motifs that had undergone a process of Muslim literary adaptation. A comparison of his narrative with that of Christian works of the same period will show that he occupied a unique position among his contemporaries. Yet perhaps more importantly, once we acknowledge the role of the biblical narrative in enhancing the work's credibility in the eyes of its readers, we gain a better sense of the cultural world of that potential Christian readership. By focusing on the biblical narrative of Ibn Baṭrīq's treatise, the article bypasses the question of its apologetic agenda and addresses instead the writer's methodology and, through this, the cultural world of his readership.